Conflicts between antidumping and antitrust law in the EC - Ingo Schmidt; Sabine Richard (Intereconomics, 1992)
Antidumping policy aims at protecting single firms or industries from distortions in trade with third countries. A broad definition of dumping can, however, lead to protectionist measures which conflict with antitrust policy. To what extent is this the case in the EC?
Keywords: 330; European Community